2010
DOI: 10.1111/j.1349-7006.2010.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein interacting with C α kinase 1 (PICK1) is involved in promoting tumor growth and correlates with poor prognosis of human breast cancer

Abstract: Protein interacting with C a kinase 1 (PICK1), which interacts with multiple different proteins in a variety of cellular contexts, is believed to play important roles in diverse pathological conditions including cancer. In this study, we attempted to investigate the correlation of PICK1 with clinicopathological features as well as prognosis of human breast cancer. In addition, we aimed at a better understanding of the biological function of PICK1 in breast cancer cell biology. As judged by semi-quantitative RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…Increased expression of PICK1 was reported in breast cancer [26]. We observed a negative correlation between PICK1 and p-Smad2 levels in breast cancer samples, indicating that PICK1 may promote breast cancer formation by restricting TGF-β signaling.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Increased expression of PICK1 was reported in breast cancer [26]. We observed a negative correlation between PICK1 and p-Smad2 levels in breast cancer samples, indicating that PICK1 may promote breast cancer formation by restricting TGF-β signaling.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that PICK1 is highly expressed in breast cancer cells [26]. To investigate whether the negative regulation of PICK1 on TGF-β signaling contributes to breast cancer development, we first examined the effect of PICK1 on the antiproliferative activity of TGF-β in breast epithelial MCF10A cells.…”
Section: Pick1 Expression Is Negatively Correlated With Tgf-β Signalimentioning
confidence: 99%
See 1 more Smart Citation
“…43 Very recently it was shown that PICK, a critical mediator of AMPAR trafficking in neuronal synapses, is overexpressed in breast cancer and antagonizes TGF-β1 signaling by promoting caveolin-dependent degradation of TβRI, thus abolishing TGF-β1-induced growth inhibition. 44,45 However, it was also reported that TβRI is a target of homeoprotein Six1 and Six1-induced upregulation of TβRI is required to switch of TGF-βI signaling to the prometastatic phenotype, such as EMT. 46 Although our study reveals that modulation of either TβRI or TβRII by PPARδ-ABCA1-Cav1 signaling provokes similar effect in prostate carcinoma cells, further studies are required to clarify whether TβRI and TβRII have differential functions in the shift of TGF-βI signaling depending on cellular context and origins.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric adenocarcinoma encompasses many subtypes with distinct genetic and biological features. Identification of new biological markers to determine the risk of poor prognosis is important for designing treatment strategies [2,3]. …”
Section: Introductionmentioning
confidence: 99%